Play conception in british postmodern novel (in the context of the ideological and cultural typology of the novel) (Eurasian Journal of Philology Science and Education, 2018)
The play conception determining the XX century culture comes from the ancient times till modernperiod. Even Plato, then Aristotle spoke of play’s thinking peculiarity and appreciated it as the main feature of mimesis. The play as a cultural event, as a part of the culture, was in the center of attention of representatives of German romanticists, tried to determine a scientific basis of it. At the beginning of the XXcentury Johan Huizinga in his work «Homo Ludens» presented the «culture as a play» conception, appreciates «a playing man» as a phenomenon. J. Huizinga’s «play conception» is shown in the postmodernistaesthetics point of view such as in the discourses of R. Barthes, J. Deleuze, Y. Kristeva, J. Baudrillard.In postmodern prose, the notions such as play with the text, play within the text, metalanguage play,and carnival trickery are based on the «culture as a play» conception. The idea of the center’s being notone but several makes the history seemed serious common, historical hero transforms into the commonperson, falls down into total irony by the postmodernist play principle. If there exists no certain truth, ifthe truth is many-sided then the idea of «the past is not the notion to be imitated» comes from here. Thehistory not imitated, «removing» of seriousness transforms into imagination. Imagination may be a playmaterial. The borders of serious things almost worshiped for many years by people go through their spiritand intellect, the removal of borders means seriousness becoming imagination. The transforming something into «play» element has the goal to show its notion hidden in the deepest levels. The postmodernistwriters based on the thoughts that human’s thought is not objective but subjective laughs at objectivismmocks its seriousness,the fore it transforms into the play element.